The drawbacks of preferential trade agreements in Asia - Heribert Dieter (Kiel Institute for the World Economy (IfW), 2012)
Preferential trade agreements are mushrooming in Asia. However, they have not been facilitating intra-regional trade as much as the supporters of these exclusive arrangements have suggested. The complexities of rules of origin - part and parcel of all preferential agreements - have resulted in low utilization rates in Asia. The key driver of trade integration in Asia has been the rise of China, and not preferential trade agreements. In the last two decades, Chinas has managed to establish itself as the indispensable trading partner in the region. In 2011, China accepted a trade deficit with its neighbouring countries whilst producing surpluses with the USA and the EU. At the same time, deeper trade integration in Asia, e.g. an Asian wide customs union, appears to be unrealistic. At this juncture, the political obstacles that hinder a deepening of co-operation are formidable. Other Asian countries like to co-operate with China, but demonstrate an even rising reluctance to enter far-reaching integration projects with Bejing.
Keywords: F14; F15; F55; 330; Regional integration; Asian co-operation; ASEAN; China; preferential trade agreements